Fragmentation and Strategic Market-Making - Laurence Daures Lescourret; Sophie Moinas (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Information technology, infrastructure enhancement, and arbitrage strategies all contributeto link trading venues in fragmented markets. Our paper highlights a new cross-market linking channel: the interdependence of liquidity providers' inventory costs. We use a two-venue duopoly model involving strategic risk-averse market-makers. Costs to provide immediacy depend on market-makers' inventory aggregated across venues, implying that absorbing a shock in one venue simultaneously changes marginal costs in all other venues. Moreover, market-makers strategically choose which shock(s) to absorb. These two forces may lead to competitive prices and enhanced liquidity. Using Euronext proprietary data, we uncover evidence for these crossmarket inventory cost linkages.
Keywords: 330